Organic Chemistry For Babies - Ferrie, Chris; Florance, Cara ([United States] : Sourcebooks Jabberwocky, an imprint of Sourcebooks Inc., 2018)
Offers a simple illustrated introduction to organic chemistry, describing how carbon, oxygen, and hydrogen atoms react differently to one another to create many unique molecule structures.--.
Cover title.
On board pages.
new kids book 2024 fall.
Keywords: Chemistry, Organic -- Juvenile literature; Board books; Board books; Chemistry, Organic; Chemistry, Organic; Board books; Board books; Juvenile works; Picture books